Factors affecting properties of fuel pellets from compaction of mixed biomass and waste plastics - Unchana Auprakul (2020)
© 2019, Int. Comm. of Agricultural and Biosystems Engineering. All rights reserved. The purpose of this research is to investigate the densified solid fuel from mixed plastic wastes which were recovered from dumpsites. Corn stover was used as natural binder of the fuel. In this study, the corn stover can bind plastic materials into the fuel using compaction. The densification of mixed plastic wastes and corn stover was investigated at 150 MPa compression pressure. The size of pellet was 8 mm in diameter and 20 mm in length. The parameters effect on the fuel properties of this research were moisture content (5%-20%w.b.), types of material, mixed plastic wastes and corn stover ratio (55:45, 65:35 and 75:25), and preheating temperatures (75°C and 100°C). Results found that corn stover could improve chemical properties (reducing sulfur and chlorine content) and physical properties of the fuel pellet. It was also found that mixed plastic wastes and corn stover was superior to corn stover pellet without plastic wastes in terms of calorific value and carbon content.